A Scale to Measure the Sustainability and Performance of Self-Help Groups - Ghai, Riya; Goel, Puneeta; Chatnani, Niti Nandini (Prabandhan: Indian Journal of Management, 2026)
Purpose : To create an extensive scale for assessing the long-term sustainability and performance of self-help groups in India. These groups are the basis of microfinance for poor communities, often the weakest sections of society. The goal of this study was to explore both the traditional and contemporary aspects of sustainability, including financial and economic empowerment, emotional well-being, and effective group coordination. Methodology : A mixed-methodology design was adopted to construct a scale. In phase 1, detailed interviews were conducted with leaders and members of self-help groups. The qualitative factors were statistically validated in phase 2 using factor analysis to support the quantitative findings. Lastly, these factors were interpreted to construct a comprehensive scale. Findings : The study examined nine key factors that measure the performance and sustainability of self-help groups. The emergence of institutional support and digital literacy was a novel finding that highlighted the growing importance of organizational support and technical expertise in sustaining the continuous existence of self-help groups. Practical Implications : The validated scale provided leaders, NGOs, the government, and self-help group promoters with an analytical tool to assess group performance, pinpoint areas for development, and create plans to enhance the effectiveness and sustainability of self-help groups. Originality : A multidimensional sustainability scale for self-help groups was developed using a mixed-method sequential exploratory research design. The study improved overall community development and access to microfinance from both theoretical and practical aspects.